O desenvolvimento da autonomia do aluno de Ciclo I, dando voz ao professor - Muzi, Beatriz (2007)
This study has as objective to know the viewpoint of two teachers of the Teaching Intrastate Network about of the dimension of their collaboration to the development of the students autonomy. The results of the research reveals that the problem is directly connected to the concept of autonomy of each one of them. The study shows, also, that is fundamental to understand which the senses and meanings of the students autonomy to the teachers. To answer the questions that we exhibit it was chosen by the theoretical methodological reference of the Social Historic Psycology in which Vygotsky is one of the central authors. Like that, it was used the boarding of the qualitative research having like instrument the questionnaire and the interview. The analysis of the dates demonstrated to be of extreme importance to understand the relation between the introduced facets, by the subjects, upon students autonomy and the pedagogical practice. To know the historic and social conditions present in the educational formation of each one of the teachers was fundamental so that the analysis could reveal the singular of the subjects. It was expected that this research can collaborate to the reflexions of the teachers as well as of the school team, about the pedagogical practice so that to possibility arguments to the amplification of the idea upon the action of the teacher in relation to the students autonomy. To conclude, we reaffirm the purpose to collaborate to the reflexions about learnings more significants, and by extension, that can have space to the transformation